Comparative Study of Legal Protection of Women's Labor From the Perspective of International Conventions, Indonesian and German Law - Lalu Hadi Adha; Baiq Sagita Salsabila; Laely Wulandari (Faculty of Law, Universitas Pekalongan, 2025)
Work related to humans, including aspects of the economy and fundamental human rights, is essential. Every individual, regardless of gender, has equal rights in the workforce. In the modern era, women are involved in forced labor, although they still face various challenges. In normative terms, protecting women's rights as workers in Indonesia is regulated by Law Number 13 of 2003 concerning Employment, alongside several other regulations and international conventions such as the ILO and CEDAW. However, there are several gaps in the framework, such as provisions that do not fully protect female workers and a lack of effective implementation of the conventions that have been ratified, which often merely reiterate the norms of the international convention. On the other hand, Germany has also ratified the convention and has more specific regulations for protecting women's rights. By comparing the laws of Indonesia and Germany, this research aims to provide recommendations for improvements and refinements in employment regulations in Indonesia. The research method employed is a normative legal study with a statutory, conceptual, and comparative approach. Based on the results of this study, it can be concluded that the regulations for protecting female workers in Indonesia and Germany have similarities and differences. In Indonesia, the protection of women is primarily outlined in the Employment Act, while in Germany, each protection category is more distinctly defined in the Constitution. Although both jurisdictions address matters such as maternity, protection from discrimination, and wage equality for equivalent work, there is a difference in the level of detail in their arrangements.